About proverbs related to ants in Africa : Diversity of the information and of their perception - (:unkn) unknown (My University, 2022)
The objective of this paper is to point out the richness of proverbs dealing with ants. First, the age and theimportance of “ants” are underlined. Next, the proverbs expressed in Africa are taken up in alphabetical order of theconcerned languages. In total, 63 proverbs appear in the present paper; they are relevant to 19 different languages.
Keywords: African Research